Obstructive sleep apnoea in people with Type 1 diabetes: prevalence and association with micro‐ and macrovascular complications. Issue 1 (25th September 2014) - Manin, G.; Pons, A.; Baltzinger, P.; Moreau, F.; Iamandi, C.; Wilhelm, J. M.; Lenoble, P.; Kessler, L.; Kessler, R.
Abstract Aims Few reports have assessed the relationship between Type 1 diabetes and sleep disorders. The purposes of our study were to determine the prevalence of obstructive sleep apnoea in Type 1 diabetes and to compare the clinical profile of people with Type 1 diabetes with or without obstructive sleep apnoea. Methods In this cross sectional study of 67 consecutive people with Type 1 diabetes, we performed polysomnography as part of their yearly check‐ups. Results In our cohort, with a mean BMI of 25.8 ± 4.7 kg/m2, the prevalence of obstructive sleep apnoea [apnoea–hypopnoea index (AHI) > 10/h] was 46%. Severe obstructive sleep apnoea (AHI ≥ 30/h) was present in 19% of the patients. We found no significant differences in age, sex, body mass index, HbA1c or Epworth sleepiness scale score between people with or without obstructive sleep apnoea. People with obstructive sleep apnoea had a longer course of diabetes mellitus (P < 0.01) and a higher prevalence of retinopathy (P < 0.01), neuropathy (P = 0.05), cardiovascular disease (P < 0.01) and hypertension (P < 0.01). The occurrence of macrovascular complications was independently associated with the presence of OSA [odds ratio (OR) 8.28; 95% confidence interval (CI), 1.56–43.97; P = 0.013] and the duration of diabetes (OR 1.08; 95% CI, 1.02–1.15; P = 0.01). Moreover, retinopathy was independently associated with OSA (OR 4.54; 95% CI, 1.09–18.82; P = 0.04) and the duration of diabetes (OR 1.09; 95% CI, 1.04–1.15; P = 0.001). Conclusions The prevalence of obstructive sleep apnoea was high in people with Type 1 diabetes. Obstructive sleep apnoea was independently associated with macrovascular complications and retinopathy. Obesity and excessive daytime sleepiness were uncommon in this population.